Analisis Pengaruh Pemasangan Kateter Urin terhadap Insidensi Infeksi Saluran Kemih di Rumah Sakit - Asbone, Asbone; Rosa, Elsye Maria; Ulfa, Maria (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Urinary tract infection (UTI) -related catheters are one of the four most common HAIs types in hospitals worldwide in addition to IDO, Pneumonia, and Primary Blood Flow Infection (IADP). UTI-related catheters are a significant cause of morbidity and mortality. The absence of data on the incidence of UTI related catheters in hospitals as an indicator is still low implementation of patient safety in hospitals. The purpose of this study to determine the incidence of urinary tract infections and germs that cause UTI. Method: This research was an analytical descriptive research using cross sectional observational quantitative design. Population and Sample of the study were catheter-attached patients as the subjects of the study through total sampling. Observation sheet urinary tract infections using this instrument are obtained from Centers for Disease Control and Prevention (CDC). Results: Of the 57 patients treated in the ward during the 209 days, seven patients with UTI were exposed, the incidence of symptomatic UTI in RS PKU Muhammadiyah Bantul was 33.49 â° from one culture of urine samples found Escherichia Coli and Candida Non Albicans. Conclusion: The incidence rate of symptomatic UTI in RS PKU Muhammadiyah Bantul is 33,49 â° and germs that cause urinary tract infection are Escherichia Coli and Candida Non Albicans.